A Vision for Universal and Standardized Access to Systems Competency Education. Issue 3 (10th October 2022) - Singam, Caitlyn A. K.
ABSTRACT: The interdisciplinary nature of systems engineering inherently means that the concept of a systems engineer is variable, requiring several types of expertise depending on the application sector and knowledge domain the individual is working in. However, regardless of industry or specialty, systems engineers are all unified by proficiency in a core set of fundamental competencies that allow them to understand and holistically work with systems. These systems thinking and systems engineering competencies are applicable by being interdisciplinary and are well‐suited to an increasingly globalized and interconnected world. However, views of systems thinking and systems engineering competencies as non‐essential supplementary skills rather than foundational ones have meant that systems thinking and systems engineering concepts are not generally included in science, technology, engineering, arts, and mathematics (STEAM) curricula until late in the educational pathway and are not always presented in a standardized manner. Consequently, under the current approach to systems thinking and systems engineering, not all individuals who can benefit from systems thinking and systems engineering education have access to it. Those who do often face substantial variability in the quality of their educational experiences. This article discusses existing issues relating to systems thinking and systems engineering competency education, as well as the efforts of the INCOSE SySTEAM Initiative towards addressing those issues and facilitating the integration of systems thinking and systems engineering competencies into STEAM curricula at all levels of education. Furthermore, this article presents a guiding philosophy for promoting universal and standardized access to systems competency education.